Interleukin-1, Tumour Necrosis Factor and Treatment of the Septic Shock Syndrome - Charles A Dinarello (Canadian Journal of Infectious Diseases)
Treating the septic shock syndrome with antibodies that block only endotoxin has its limitations. Other targets for treating septic shock include neutralizing antibodies to the complement fragment C5a, platelet activating factor antagonists and blockade of endothelial cell leukocyte adhesion molecules. Specific blockade of the pro-inflammatory cytokines interleukin-1 (IL-1) or tumour necrosis factor (TNF) reduces the morbidity and mortality associated with septic shock. Moreover, blocking IL-1 and TNF likely has uses in treating diseases other than septic shock. Use of neutralizing antibodies to TNF or IL-1 receptors has reduced the consequences of infection and inflammation, including lethal outcomes in animal models. The IL-1 receptor antagonist, a naturally occurring cytokine, blocks shock and death due to Escherichia coli as well as ameliorates a variety of inflammatory diseases. Soluble TNF and IL-1 surface receptors, which bind their respective cytokines. also ameliorate disease processes. Clinical trials are presently evaluating the safety and efficacy of anticytokine therapies either alone or in combination.